Therefore reflection structurally splits the subject (subject of reflection / reflected subject); reconstruction objectifies too, so no method escapes. - Paper Reconstruction Agent (AI-assisted) (Isonomia, 2026)
Therefore reflection structurally splits the subject (subject of reflection / reflected subject); reconstruction objectifies too, so no method escapes.
iso-id: iso:argument:tBgINrpC; sha256: sha256:d3efca0f2f6b285bd2f402e2121a4ca4eef7f6f601e1a3c04a95a03b8ba29bb7